2018
DOI: 10.1159/000492378
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Bilirubin with a New Adsorbent System: In Vitro Kinetics

Abstract: Background/Aims: Many potentially toxic molecules accumulate in the blood during hepatic dysfunction. In clinical practice, it is very difficult to remove bilirubin, the most widely studied toxin, and particularly the unconjugated form, strongly albumin-bound. The aim of this in vitro study was to assess irreversible bilirubin adsorption as a protein-bound compound marker, using Cytosorb® (Cytosorbents Corp.), a new hemoadsorption device designed to remove cytokines. Methods: We performed 4 in vitro experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 19 publications
(45 reference statements)
3
38
0
Order By: Relevance
“…In the literature, Schädler and coworkers [47] showed a limited albumin loss from baseline after the treatments, indicating that the device had no significant impact on these values. Moreover, Gemelli and coworkers [23] specifically studied the behavior of the investigated adsorbent material regarding protein-bound hepatic toxins, such as bilirubin, observing the ability to irreversibly adsorb bilirubin without affecting albumin, which remained stable (changes less than 5%). Apart from these experiences, we are not aware of any other study focused on albumin behavior with the DVB-PVP sorbent or any comparative studies among different extracorporeal techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, Schädler and coworkers [47] showed a limited albumin loss from baseline after the treatments, indicating that the device had no significant impact on these values. Moreover, Gemelli and coworkers [23] specifically studied the behavior of the investigated adsorbent material regarding protein-bound hepatic toxins, such as bilirubin, observing the ability to irreversibly adsorb bilirubin without affecting albumin, which remained stable (changes less than 5%). Apart from these experiences, we are not aware of any other study focused on albumin behavior with the DVB-PVP sorbent or any comparative studies among different extracorporeal techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In this field, the most promising adsorbent materials are based on divinylbenzene coated with polyvinylpyrrolidone (DVB-PVP) or cellulose with hexadecyl chains for their high hydrophobic nature and biocompatibility, making them appropriate for the direct use in whole blood. These materials have been reported to remove molecules with chemical characteristics similar to PBUTs, such as albumin-bound bilirubin [22,23] or hydrophobic cytokines [24,25], in several clinical settings. These compounds have a hydrophobic characteristic similar to the microbial-derived metabolites, justifying the rationale for the use of DVB-PVP or cellulosic resins for the absorption of either IS and PCS.…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro analysis revealed the efficacy of CytoSorb in eliminating bilirubin, with marginal loss of albumin. 21,22 CytoSorb is a promising liver support device, due to its capacity to adsorb bilirubin and its confirmed capability to modulate the cytokines involved in hepatic dysfunction. In patients with multiorgan failure after surgery, the system is a promising therapeutic choice for critically ill and may help in cytokine reduction, improving organ function.…”
Section: Discussionmentioning
confidence: 99%
“…The device breaks the binding between unconjugated bilirubin and albumin, allowing the device to absorb the bilirubin molecule without affecting patients' albumin serum concentrations. The in vitro study from 2018 confirmed bilirubin removal by Cytosorb without affecting the albumin serum concentration during the process, which was a therapeutic issue with some other methods [31]. The case of cardiac surgery patient showed a bilirubin drop from 24.5 mg/dL to 10.8 mg/dL after three days of Cytosorb therapy [32].…”
Section: State Of Knowledgementioning
confidence: 92%